INSTITUTIONAL TRANSFORMATION OF CUSTOMARY VILLAGES IN CENTRAL MALUKU: INDIGENOUS GOVERNANCE, IDENTITY POLITICS, AND LAND RIGHTS IN TULEHU AND HARUKU - Bisri As Shidiq Latuconsina; Jusuf Madubun; Mike J. Rolobessy (SOSIOEDUKASI, 2025)
This study examines the institutional transformation of customary villages in Central Maluku, focusing on Tulehu and Haruku. It employs a critical qualitative approach using a case study method, combining in-depth interviews with customary leaders, Saniri members, village officials, and local government representatives, participatory observation in customary rituals and village administration, and analysis of official documents, village regulations, historical archives, and maps. Data were analyzed using critical discourse analysis, social mapping, and triangulation to understand the interactions between indigenous governance and state bureaucracy. The findings indicate that the transformation of adat institutions is a complex social process involving negotiations between customary values, state regulations, and identity politics. Both Tulehu and Haruku retain traditional structures—Raja (Upu), Saniri Negeri, and Soa—but differ in integration with formal administration. Tulehu maintains strong social and spiritual authority but faces limited documentation, overlapping territorial claims, and slower formal recognition. Haruku has systematically integrated adat and church norms into village governance, with clear boundaries and institutionalized structures. Interactions with the state are ambivalent: while legal recognition is granted, bureaucratic procedures constrain adat autonomy. Both communities adopt adaptive and collaborative strategies to sustain governance, including revitalizing deliberative forums, strengthening religious leadership, documenting territorial boundaries, and managing resources through traditional practices in coordination with government and church authorities. Overall, the study shows that adat transformation in Central Maluku represents a negotiation between preserving cultural identity and engaging with modern governance structures, highlighting the importance of both local autonomy and administrative alignment for sustainable indigenous law communities.